Deregulation And Foreign Exchange Risk Management Issues And Implications For Indonesian Firms - Batten, Jonathan (The International Journal of Accounting and Business Society, 1994)
Recent international studies provide insights into the foreign exchange (FX) risk management practices of large firms. The findings suggest that multinational firms behave similarly in their risk management practices irrespective of head office location. Though there is a preference for cash based â€œphysicalâ€ FX products (such as spot and forward contracts), there appears to be a trend towards â€œsynthetic or derivativeâ€ products, including options and futures. This shift in product preference reï¬‚ects the globalisation and deregulation of domestic ï¬nancial markets during the l980â€™s. Local differences in behavior may be attributable to regional variations in financial market structure rather than cultural factors. The Indonesian financial market has recently begun the process of deregulation. It is now strategically placed to capitalize on the internationalization of Indonesian industry. Industry will now require a variety of financial risk management products and services. Unless the Indonesian financial market provides these services, Indonesian firms will take this business to other regional ï¬nancial markets in Kuala Lumpur and Singapore. An understanding of firm risk management practices is also important for FX price-makers; the Indonesian financial and banking sector, since the corporate FX risk manager is primarily a price-taker from the price-making wholesale over-the-counter and (OTC) and interbank cash market.